Who are “the least?” Ἐλάχιστος (Mt 25:31-46) – a hermeneutical reconsideration - CIUCIU, Hrisostom (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
The present paper deals with the interpretation of one of the Matthean texts that still raises problems to modern exegesis, namely the one relating to the Last Judgment (Mt 25:31-46), and this because of a term – ἐλάχιστος (v. 40) – translated with “the least”. The question to which the author tries an answer is: “Who are the little ones?” The approach of the work is not so much one of an exegetical nature, but it is of a hermeneutical nature. Beyond the difficulties that modern exegesis seems to have failed to overcome, the real challenge is the spiritual interpretation of this text, an interpretation which depends very much on identifying those who are “the least”. This work attempts to harmonize the textual exegesis with the patristic interpretation, having the stated purpose of applying this text to the spiritual life, both relating to the person and community.